Increase the adoption of Agent-based Cyber-Physical Production Systems through the Design of Minimally Invasive Solutions - Rocha, André Dionísio Bettencourt da Silva Parreira (2019)
During the last few years, many approaches were proposed to offer companies the ability to have dynamic and flexible production systems. One of the conventional ap-proaches to solving this problem is the implementation of cyber-physical production sys-tems using multi-agent distributed systems. Although these systems can deal with several challenges faced by companies in this area, they have not been accepted and used in real cases. In this way, the primary objective of the proposed work is to understand the chal-lenges usually found in the adoption of these solutions and to develop a strategy to in-crease their acceptance and implementation. Thus, the document focuses on the design and development of cyber-physical produc-tion systems based on agent approaches, requiring minimal changes in the existing pro-duction systems. This approach aims of reducing the impact and the alterations needed to adopt those new cyber-physical production systems. Clarifying the subject, the author presents a definition of a minimal invasive agent-based cyber-physical production system and, the functional requirements that the designers and developers must respect to imple-ment the new software. From these functional requirements derived a list of design princi-ples that must be fulfilled to design and develop a system with these characteristics. Subsequently, to evaluate solutions that aim to be minimally invasive, an evaluation model based on a fuzzy inference system is proposed, which rank the approaches accord-ing to each of the design principles and globally. In this way, the proposed work presents the functional requirements, design principles and evaluation model of minimally invasive cyber-physical production systems, to increase the adoption of such systems.